2015
DOI: 10.1016/j.copbio.2014.11.025
|View full text |Cite
|
Sign up to set email alerts
|

HKT transporters mediate salt stress resistance in plants: from structure and function to the field

Abstract: Plant cells are sensitive to salinity stress and do not require sodium as an essential element for their growth and development. Saline soils reduce crop yields and limit available land. Research shows that HKT transporters provide a potent mechanism for mediating salt tolerance in plants. Knowledge of the molecular ion transport and regulation mechanisms and the control of HKT gene expression are crucial for understanding the mechanisms by which HKT transporters enhance crop performance under salinity stress.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
114
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 193 publications
(117 citation statements)
references
References 67 publications
1
114
0
2
Order By: Relevance
“…Genes related to proline synthetase and chlorophyll binding protein are up-regulated in barley under salt stress [20]. Also, the genes PtSOS2, NHXs and HKTs have been observed to play an important role in improving plant salt tolerance by controlling ion balance through ion transport [10,21,22]. Comparative genomics regarding salt tolerance between Arabidopsis and salt cress were analysed using cDNA microarrays, and the results showed that the stronger salt tolerance of salt cress may be due to a large number of known abiotic and biotic stress-inducible genes, including Fe-SOD, P5CS, PDF1.2, AtNCED, and SOS1, and those of P-protein and beta-glucosidase, which were expressed at high levels [23].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Genes related to proline synthetase and chlorophyll binding protein are up-regulated in barley under salt stress [20]. Also, the genes PtSOS2, NHXs and HKTs have been observed to play an important role in improving plant salt tolerance by controlling ion balance through ion transport [10,21,22]. Comparative genomics regarding salt tolerance between Arabidopsis and salt cress were analysed using cDNA microarrays, and the results showed that the stronger salt tolerance of salt cress may be due to a large number of known abiotic and biotic stress-inducible genes, including Fe-SOD, P5CS, PDF1.2, AtNCED, and SOS1, and those of P-protein and beta-glucosidase, which were expressed at high levels [23].…”
Section: Introductionmentioning
confidence: 96%
“…Therefore, studying the mechanism of salt tolerance is becoming increasingly important. Many researchers have studied the salinity-tolerance mechanisms of plants, such as ion balance, osmotic adjustment, antioxidant protection, and transcript profiling [8][9][10][11]. Salinity tolerance is a multiple gene-associated mechanism that is controlled by many genes involved in different processes, such as ion compartmentalization, extrusion and selectivity; the synthesis of metabolites; and the scavenging of reactive oxygen species (ROS) [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Several members of HKT gene subfamily in rice, including OsHKT1;1, OsHKT1;3, OsHKT1;4, and OsHKT1;5 have also been implicated in salt tolerance in rice (Hamamoto et al, 2015). All these members function as a Na + influx transporter but have different expression patterns.…”
mentioning
confidence: 99%
“…Este resultado denota que, aunque existió interferencia nutricional Na + /K + , existió acumulación activa del potasio, quizás por su importancia en la actividad enzimática fundamentalmente y por la actividad en la osmorregulación (Hamamoto et al, 2015). Algunos estudios demuestran que en condiciones de salinidad ocurre una disminución de los valores de potasio por la escasa selectividad del antitransportador Na + /K + cuando la concentración de sodio es considerablemente alta.…”
Section: Contenido Catiónico En Diferentes óRganosunclassified
“…En las raíces, los solutos que entran siguiendo el flujo transpiratorio, se mueven por el apoplasto, y atraviesan la membrana de una célula radical, continúan su transporte por el simplasto hasta alcanzar el xilema (Hamamoto et al, 2015). En teoría, el movimiento de Figura 3 -Determinación de cationes por microanálisis realizado en la parte más inferior de parte basal de la hoja (a), parte media (b) y parte próxima al ápice de la hoja (c) de la variedad de trigo Cuba-C-204 en un medio salino con 88 mM de NaCl…”
Section: Contenido Catiónico En Diferentes Secciones De óRganosunclassified